Grasshopper optimization algorithm for optimal load frequency control considering Predictive Functional Modified PID controller in restructured multi-resource multi-area power system with Redox Flow Battery units. (August 2019) - Nosratabadi, Seyyed Mostafa; Bornapour, Mosayeb; Gharaei, Mohammad Abbasi
Abstract: Load frequency control (LFC) is a well-established issue in design and operation of power systems considering to the extension, restructuring, and complexity of the interconnected power systems and also the emergence utilization of renewable energy resources. This paper studies the frequency control of multi-area multi-source power system based on the importance of the LFC in the stability of the power system which includes various generation units of thermal, hydroelectric, wind, natural gas and diesel under the restructured environment. In this system, non-linear physical constraints, governor dead band (GDB) and generation rate constraint (GRC) are considered. In this paper, a new Predictive Functional Modified PID (PFMPID) controller is proposed that the effectiveness of this controller is verified compared to the traditional one. In order to optimize and demonstrate the superiority of the proposed control method, Grasshopper Optimization Algorithm (GOA) is proposed as a suitable solution. To further improve the performance of the under study system, the use of the Redox Flow Battery (RFB) energy storage unit has also been proposed. Since the operation evaluation of the proposed process is necessary in different system conditions, the performance of the proposed method is studied under various disturbances and simulation results are presented. Highlights: A new PFMPID controller using an appropriate optimization algorithm is proposed for LFC. The wind and diesel generation units are proposed in some areas to improve the LFC performance. The Grasshopper Optimization Algorithm is proposed to optimize the control parameters. In order to further improve the LFC performance, the Redox Flow Battery units are considered. The effectiveness of the proposed method is investigated under various possible disturbances.